Electrodermal activity as a measure of emotions in media accessibility research: methodological considerations - Anna Matamala; Olga Soler-Vilageliu; Gonzalo Iturregui-Gallardo; Anna Jankowska; Jorge-Luis Méndez-Ulrich; Anna Serrano Ratero (JoSTrans: The Journal of Specialised Translation)
This article proposes electrodermal activity (EDA) as a new objective measure for experimental studies in media accessibility. It first presents a theoretical framework in which the concept of emotion and its categorisation are presented. It then explains how EDA can be used to measure emotional reaction: the article reports on experimental design, participant selection, stimuli preparation, data collection devices, experimental procedure and data analysis. It also discusses briefly how EDA can be combined with other measures. Overall, the article provides a general methodological framework for the implementation of electrodermal activity as a measure of emotions in media accessibility research.